2020
DOI: 10.3390/ijerph17031076
|View full text |Cite
|
Sign up to set email alerts
|

Computing and Oral Health: Mobile Solution for Collecting, Data Analysis, Managing and Reproducing Epidemiological Research in Population Groups

Abstract: Epidemiological inquiries study and evaluate the health status of the population. For dental caries, the World Health Organization (WHO) recommends the DMFT and DMFS indexes, which represent the sum of the decayed, missing and filled teeth, divided by the population studied. Traditionally these surveys are conducted using cellulose paper sheet. This study describes the development and presents the field performance of NutriOdonto, a software created for an Oral Health Survey carried out in 2018 and 2019 involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The use of electronic health records may replace papers in dental schools but those institution must always provide patients an electronic copy of data recorded in EHRs, complying with the Privacy Rule by an e-mail or any other electronic way [17,25]. Other advantages of EHRs implementation are documentation quality and reduction of medical errors [77].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of electronic health records may replace papers in dental schools but those institution must always provide patients an electronic copy of data recorded in EHRs, complying with the Privacy Rule by an e-mail or any other electronic way [17,25]. Other advantages of EHRs implementation are documentation quality and reduction of medical errors [77].…”
Section: Resultsmentioning
confidence: 99%
“…Reed, et al, reported an interesting comparison between students (n = 386) before and during the EHRs utilization, which it may impact positively student's critical thinking associated with diagnostic system terminology [70]. Quality of information and care may also be improved utilizing dental record system by planning actions in oral diseases prevention and health promotion and clinical decision support [17,67].…”
Section: Resultsmentioning
confidence: 99%
“…The presented developments in this field can be classified according to the following categories such as reference books [1], educational as well, those that remind you of brushing your teeth [2], those that teach you to brush your teeth [3][4][5], questionnaires [6][7][8], those that aimed at managing the dental journal and planning the work process [9,10], diet diaries [11]. There is the latest study that use an artificial intelligence to detect dental diseases using the analysis of panoramic images in real time [12].…”
Section: Analysis Of the Latest Researchmentioning
confidence: 99%
“…Previous research has developed a smartphone application for measuring the DMF-T index and the Community Periodontal Index (CPI). 2 However, the development of mobile dental application tailored specifically for on elementary schoolchildren in Indonesia is still limited. Existing mobile applications mostly emphasize dental knowledge elements, whereas this study's innovation focuses on developing a game-based approach for self-examination of oral health problems.…”
Section: Introductionmentioning
confidence: 99%